The multiple sclerosis gut microbiota: A systematic review - Mirza, Ali; Forbes, Jessica D.; Zhu, Feng; Bernstein, Charles N.; Van Domselaar, Gary; Graham, Morag; Waubant, Emmanuelle; Tremlett, Helen (Multiple sclerosis and related disorders, 2020)
•No major differences in the overall gut microbiota composition in MS cases vs. controls.•Abundance of six taxa differed in MS cases vs. controls, similarly observed across 2 ≥ studies.•Studies were generally too modest in size to adequately assess potential effect modifiers. To systematically review and synthesize the literature on the multiple sclerosis (MS) gut microbiota composition as compared to persons without MS. We systematically searched MEDLINE, EMBASE, and Web of Science databases for relevant published articles (2008–2018). Of 415 articles identified ten fulfilled criteria. All studies used a case-control design, six sourced participants from the US, two Germany, one Italy, and one Japan. Nine focused exclusively on adults and one on children, totaling 286 MS and 296 control participants. Over 90% of cases had relapsing-remitting MS; disease duration ranged from 10.6 ± 6.5 months to 15.3 ± 8.6 years (mean±SD). Nine studies examined stool and one evaluated duodenal mucosa. Diverse platforms were used to quantify microbes: Illumina MiSeq, Roche 454, microarray, and fluorescence in situ hybridization. None of eight studies reported a significant alpha-diversity differences between cases and controls. Two of seven studies reported a difference in beta-diversity (P ≤ 0.002). At the taxa-level, ≥2 studies observed: lower relative abundance of Prevotella, Faecalibacterium prausnitzii, Bacteroides coprophilus, Bacteroides fragilis, and higher Methanobrevibacter and Akkermansia muciniphila in MS cases versus controls. Exposure to an immunomodulatory drug (IMD), relative to no exposure, was associated with individual taxonomic differences in three of three studies. Gut microbiota diversity did not differ between MS cases and controls in the majority of studies. However, taxonomic differences were found, with consistent patterns emerging across studies. Longitudinal studies are warranted to elucidate the relationship between IMD exposure and differences in the gut microbiota composition.